A New Direction in Ophthalmic Development: Nanoparticle Drug Delivery Systems - Yordanova Andonova, Velichka (Current Pharmaceutical Design, 2016)
The purpose of each dosage form is to provide an optimal therapeutic effect with a minimum dose and with minimal side effects. This is particularly relevant for drugs that require systemic administration, higher dosing and/or show lower bioavailability. Тhe eye as an anatomical structure is an extremely protected organ. In this regard, providing an optimal bioavailability in the eye tissues, resulting in the desired therapeutic effect represents a major challenge. This is especially true for the treatment of diseases, affecting the posterior segment after topically administered drug formulations. The use of nano- and microcarriers of drug substances may be an appropriate technological approach, to provide a high bioavailability of the drug substance for a certain interval of time at the right place. The purpose of this review is to indicate how nano- and microcarriers of drug substances can solve the problems with the drug delivery in the ocular tissues, to indicate the possible hazards and side effects, depending on the polymer nature and route of administration, and to visualize the future potential of these carriers in the pharmaceutical practice.
Keywords: proniosomes